Numerical and Experimental Investigation on Tensile Properties of Natural-Sand Reinforced Polypropylene - A. N., Oumer; M. S., Idris; N. M. M., Ammar; Kurniawan, Tedi (Trans Tech Publications, Switzerland, 2015)
Reinforced polymer composites are replacing metals in many engineering fields due to their high strength to weight ratio, low cost, and resistance to corrosion. In this study, the tensile properties of natural-sand particle reinforced polypropylene composites obtained by means of numerical method were compared with the experimental observations. Rectangular samples were prepared by heating the natural sand and polypropylene (PP) mixture at the melting temperature of PP and cooling in a rectangular mold. During cooling, pressure was applied on the upper part of the mold to avoid voids and shrinkages on the final sample. The concentration of the sand was varied as 5%, 10%, 15%, 20%, and 30% by weight. Then the samples were tested with 3-Point Bending and Universal Tensile Testing Machines to obtain the respective values of flexural and tensile properties of the composite samples. The numerical simulation was performed by using ANSYS software. For the simulation, structured mesh was constructed with 7500 elements and 36466 nodes. The experimental results indicated that the yield stress values dropped gradually from 21.62 MPa for 5% by weight to 8.01 MPa for 30% which leads to a conclusion that the higher the percentage of the sand particle reinforcement, the lower the tensile strength of the composite would be. Moreover, both the numerical and experimental results showed a linear increase in deflection with the increments of the applied load. These results are as expected and they confirm with the theoretical behavior of a bar subjected to axial loading. Hence, this study could assist in decisions regarding the design of reinforced composite products.